Analysing On-Time Performance of Public Bus Service at Northern Peninsular Malaysia - Azlan N.N.I.M.; Norhisham S.; Bakar M.F.A.; Shkuri N.S.M.; Fauzi W.A.F.W.M.; Masjuki S.A.; Ramli M.Z.; Samsudin S.S. (Springer Science and Business Media Deutschland GmbH, 2023)
Bus transportation; Buses; Traffic congestion; Bus services; Congestion delay; Energy-consumption; Malaysia; Northern peninsular malaysia; On-time performance; Public bus; Public transportation; Quality-of-service; Uncertainty; Quality of service